Educação superior no século XXI e a reforma universitária brasileira - Macedo, Arthur Roquete de; Trevisan, Ligia Maria Vettorato [UNESP]; Trevisan, Péricles; Macedo, Caio Sperandeo de (Fundação CESGRANRIO, 2005)
Tomando como referência a evolução e as características do sistema brasileiro de educação superior discute-se neste artigo os fundamentos de uma efetiva reforma da educação superior. Procura-se mostrar que a adequação desse sistema para o enfrentamento dos desafios da sociedade do conhecimento, em um país como o Brasil, deve necessariamente resolver três questões: a modernização do sistema, o efetivo aprimoramento da qualidade da educação brasileira em todos os níveis, graus e modalidades e a democratização do ensino promovendo a inclusão social.

Tomando como referencia la evolución y las características del sistema brasileño de educación superior, en este artículo se discuten los fundamentos de una efectiva reforma de la educación superior. Se intenta mostrar que la adecuación de este sistema para el enfrentamiento de los desafíos de la sociedad del conocimiento, en un país como Brasil, se deben necesariamente resolver tres cuestiones la modernización del sistema, la efectiva mejora de la calidad de la educación brasileña a todos los niveles, grados y modalidades, y, la democratización de la enseñanza promoviendo la inclusión social.

This paper aims to present the essential basis for an effective higher education reform. The strategies chosen by the authors to develop and to construct their proposals are based on studies of evolution and special features of the Brazilian Higher Education System. By analyzing this special and highly complex system the authors could conclude that in order to fit the challenges which emerge from the knowledge society the higher education system reform adjusted to a country like Brazil has to be reorganized in order to present solutions to three main questions: the system modernization, the improvement of the quality of the whole brazilian education system and the promotion of social inclusion through the access democratization.
Educación superior en el siglo XXI y la reforma universitaria brasileña
Higher education: the XXI century and the Brazilian university reform
Keywords: Educação superior brasileira; Reforma universitária; Reforma do ensino superior; Educação superior; Educación Superior Brasileña; Reforma Universitaria; Reforma de la Enseñanza Superior; Educación Superior; Brazilian higher education; University reform; Higher education reform.; Brazilian system of higher education